1982
DOI: 10.1007/bf00120678
|View full text |Cite
|
Sign up to set email alerts
|

Community stability, complexity and species life history strategies

Abstract: The essence of the contradiction between traditional ecological complexity-stability hypothesis and recent theoretical results is clarified. The distinction between resilience and resistance is stressed. The possibilities of field verification of May's model are discussed. No satisfactory method for estimation of connectance and mean interaction strength in plant communities has been found. Relation between these parameters and stability in real communities remains an open question. The relation between connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
156
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(171 citation statements)
references
References 47 publications
12
156
0
3
Order By: Relevance
“…There are several components of population stability (Harrison 1979), among which temporal stability (also referred to as constancy, or its opposite, temporal variation or variability) is probably the most frequently studied. It has been suggested that slow-growing and long-lived species might respond less rapidly to environmental changes, conferring them greater population temporal stability (Lepš et al 1982, MacGillivray et al 1995, Grime et al 2000. This trend has been documented in insects, where species with low population growth rate exhibited greater population temporal stability (Spitzer and Lepš 1988); similar patterns have also been suggested for long-living adults in plants (Chesson 2000).…”
Section: Introductionmentioning
confidence: 77%
“…There are several components of population stability (Harrison 1979), among which temporal stability (also referred to as constancy, or its opposite, temporal variation or variability) is probably the most frequently studied. It has been suggested that slow-growing and long-lived species might respond less rapidly to environmental changes, conferring them greater population temporal stability (Lepš et al 1982, MacGillivray et al 1995, Grime et al 2000. This trend has been documented in insects, where species with low population growth rate exhibited greater population temporal stability (Spitzer and Lepš 1988); similar patterns have also been suggested for long-living adults in plants (Chesson 2000).…”
Section: Introductionmentioning
confidence: 77%
“…EP such as primary productivity, nutrient cycling, and trophic transfer to herbivores (3,10,(14)(15)(16)(17)(18)(19)(20) that appear consistent across biomes, ecosystems, and floras (15)(16)(17)(18)(19). Links of local CWM of such plant traits with biogeochemistry-derived ES have been documented in several cases (21)(22)(23)(24)(25).…”
Section: The Mass Ratio Hypothesis: a Cornerstone Of Fd-ep Relationshipsmentioning
confidence: 99%
“…For example, early-and late-successional communities differ not only in their stability characteristics, but also in their species richness. Nevertheless, both differences are dependent on the composition of prevailing life-history strategies in a community (Lepš et al 1982, Lepš 1990). This might suggest that an experimental approach would be more profitable.…”
mentioning
confidence: 99%